Stratigraphic and cartographic review in the western part of Bauru Basin – Brazil - (Upper Cretaceous): implications for the depositional model - Liliane Maia Tcacenco-Manzano; Luiz Alberto Fernandes (Journal of Maps)
Bauru Basin (Upper Cretaceous) spans 190,000 km² in western segment, Mato Grosso do Sul and Goiás states, Brazil. The Supersequence is a predominantly sandy siliciclastic unit. In Mato Grosso do Sul state a substantial portion of the sedimentary supersequence was considered indivisible. This research, based on regional field surveys, presents updates to the geological map, depositional model, and lithostratigraphic chart of the western Bauru Basin. In Mato Grosso do Sul, the Rio Paraná Formation was identified, directly overlaying the Serra Geral Group in the south/southwest, and the Botucatu Formation on north/central region. The Santo Anastácio Formation outcrop area was found to be smaller than previously mapped, showing lateral contacts with the Rio Paraná and Vale do Rio do Peixe formations. The Vale do Rio do Peixe Formation, conversely, now exhibits a larger mapped area. Additionally, the Marília Formation were discovered in São Gabriel do Oeste-MS, previously marked as detrital-lateritic cover.